2015
DOI: 10.1111/anae.13015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Aids in Medicine Assessment Tool (CMAT): preliminary validation of a novel tool for the assessment of emergency cognitive aids

Abstract: Summary Applying human factors principles to the design of clinical emergency guidelines is important. The UK Civil Aviation Authority uses a Checklist Assessment Tool for evaluating the content and usability of emergency drills before introduction into service on aircraft. We hypothesised that this model could be used to develop a generic medical tool. A three‐stage modified Delphi process was used to adapt the above tool for use in designing medical emergency guidelines. The resulting Cognitive aids in Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
(32 reference statements)
2
16
0
Order By: Relevance
“…Even within the required competencies set out by the GMC in 'Outcomes for Graduates', the standards suggest that learning skills for good doctor-patient communication, especially difficult communication with vulnerable patients, is prioritised over communication with colleagues during undergraduate training. The problem is that reducing communication to a list of required exchanges carries the risk of emphasising process rather than outcome [9,10]. In addition, the focusing of communication skills on community-based scenarios and the exclusion of acute care physicians from the teaching process appears to have led to the prioritisation of careful, structured exchanges in a relaxed consultation over the rapid achievement of shared understanding between professionals in an emergency.…”
Section: Communication Skillsmentioning
confidence: 99%
“…Even within the required competencies set out by the GMC in 'Outcomes for Graduates', the standards suggest that learning skills for good doctor-patient communication, especially difficult communication with vulnerable patients, is prioritised over communication with colleagues during undergraduate training. The problem is that reducing communication to a list of required exchanges carries the risk of emphasising process rather than outcome [9,10]. In addition, the focusing of communication skills on community-based scenarios and the exclusion of acute care physicians from the teaching process appears to have led to the prioritisation of careful, structured exchanges in a relaxed consultation over the rapid achievement of shared understanding between professionals in an emergency.…”
Section: Communication Skillsmentioning
confidence: 99%
“…Based on ILCOR Consensus on Science with Treatment Recommendations, the HBB algorithm can link directly from positive-pressure ventilation into the more advanced ILCOR algorithm when the response to bag-mask ventilation is inadequate and expertise and equipment are available [14]. In contrast, the intermediate algorithm trades the simplicity of graphic design and limited steps for multiple, text-based conditional steps and contingencies, which violate many of the principles of human factors design [15]. Decision-making will vary with the individual capacities of team members and equipment available in a particular facility, making standardized training difficult and complicating teamwork and communication.…”
mentioning
confidence: 99%
“…Colour is good for discrimination, but high contrast is required. 57 2. High-contrast text and background for maximum visibility.…”
Section: Record Form (Part 1)mentioning
confidence: 99%
“…The outcome of this evaluation revealed that the most prevalent cognitive aid is the neonatal resuscitation algorithm. 87 In Paper 1, I provide a detailed evaluation of the ILCOR algorithm and four variations by member councils against CMAT design criteria, 57 and against medical device guidelines. 33 The outcome of this study was that the ILCOR algorithm had moderate adherence to both CMAT criteria and the medical device guidelines, but that design variations reduced the adherence to these guidelines.…”
Section: Phase 1 Current Team Training and Interventions: Crm And Comentioning
confidence: 99%
See 1 more Smart Citation